2022
DOI: 10.3390/membranes12101014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Zinc Dendrites Realized by a β-P(VDF-TrFE) Nanofiber Layer in Aqueous Zn-Ion Batteries

Abstract: Uncontrollable Zn dendrite formations and parasitic side reactions on Zn electrodes induce poor cycling stability and safety issues, preventing the large-scale commercialization of Zn-ion batteries. Herein, to achieve uniform Zn deposition and suppress side reactions, an electrospun ferroelectric poly(vinylidene fluoride-co-trifluoroethylene) copolymer, a P(VDF-TrFE) nanofiber layer, is introduced as an artificial solid–electrolyte interface on a Cu substrate acting as a current collector. The aligned molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The polar nitrile groups present in the PAN nanofibers facilitate the uniform nucleation of zinc and prevent the growth of dendrites. As shown in Figure 8b, the symmetrical cell test demonstrates that the Zn@PAN-Cu electrode has extended cycling stability without a short circuit happening after approximately 270 h. Kim's group [105] also reported that an electrospun ferroelectric poly(vinylidene fluoride-co-trifluoroethylene) copolymer (P(VDF-TrFE)) nanofiber layer, denoted as PNF, can yield homogeneous Zn deposition and inhibit side reactions. In addition, Zhao's group [106] demonstrated that the polybenzimidazole (PBI) nanofibers with abundant N-containing functional groups not only allow uniform Zn nucleation on the Cu surface but also facilitate the uniform transport of Zn 2+ ions, facilitating the uniform deposition of zinc on the 3D porous framework.…”
Section: Functional Interlayersmentioning
confidence: 90%
“…The polar nitrile groups present in the PAN nanofibers facilitate the uniform nucleation of zinc and prevent the growth of dendrites. As shown in Figure 8b, the symmetrical cell test demonstrates that the Zn@PAN-Cu electrode has extended cycling stability without a short circuit happening after approximately 270 h. Kim's group [105] also reported that an electrospun ferroelectric poly(vinylidene fluoride-co-trifluoroethylene) copolymer (P(VDF-TrFE)) nanofiber layer, denoted as PNF, can yield homogeneous Zn deposition and inhibit side reactions. In addition, Zhao's group [106] demonstrated that the polybenzimidazole (PBI) nanofibers with abundant N-containing functional groups not only allow uniform Zn nucleation on the Cu surface but also facilitate the uniform transport of Zn 2+ ions, facilitating the uniform deposition of zinc on the 3D porous framework.…”
Section: Functional Interlayersmentioning
confidence: 90%
“…To our knowledge, the functional groups of organic AILs strengthen the desolvation of hydrated Zn 2+ to regulate the Zn 2+ flux and Zn nucleation at the anode‐electrolyte interfaces. [ 106,107 ] Considering the limits of a single component, organic‒organic composite AILs further enhance the interfacial adsorption of Zn ions and groups and modulate Zn nucleation and growth due to the combination of multiple groups. Li's group reported a binary blend layer consisting of polyacrylamide (PAM) and polyvinylpyrrolidone (PVP) (Figure 6d).…”
Section: Optimization Strategies Of the Zn Anode‐electrolyte Interfacesmentioning
confidence: 99%